1D Rodlike mBiVO4 Mesocrystals: Preparation, Formation Mechanism and Photocatalytic Performance. Issue 23 (18th June 2019) - Zhao, Guosheng; Zheng, Xuchen; Qian, Jingyi; Wang, Mengyao; Cao, Xinyu; Teng, Honghui; Liu, Wei
Abstract: Mesocrystals have attracted more attention owing to their unique structures and properties. Nevertheless, facile and green synthesis of well‐defined mesocrystals still remains a significant challenge. Herein, one‐dimensional (1D) rodlike monoclinic scheelite phase BiVO4 ( m BiVO4 ) mesocrystals having superstructures orderly assembled by m BiVO4 nanoparticle building blocks, were created via a facile solvothermal method in the glycerol (Gly)/water mixed solvent without any additives. By adjusting the dosage of Gly and pH value of the reaction system, the microstructure of BiVO4 can be accurately regulated. The obtained samples were carefully characterized by XRD, SEM, TEM, HRTEM, BET, FTIR, PL and UV‐vis techniques. The lower pH value and the higher dosage of Gly were propitious to form rodlike m BiVO4 mesocrystals. Of course, the kind and concentration of reaction species in the system and the assembly force were affected by the dosage of Gly and pH value. The possible formation mechanism of the BiVO4 mesocrystals was proposed on the basis of these analyses. The optimized rodlike m BiVO4 mesocrystal prepared with 8 mL of Gly at pH 2 exhibited the highest photocatalytic degradation activity for methylene blue (MB) under simulated sunlight irradiation, which could be attributed to its phase composition, higher surface area, stronger light absorption and 1D rodlike morphology with short L/D ratio which may increase the separation efficiency of photogenerated electrons and holes. Abstract : The optimized rodlike m BiVO4 mesocrystal could be obtained by a facile solvothermal method with 8 mL of Gly at pH 2, and then exhibited the highest photocatalytic degradation activity for MB under simulated sunlight irradiation, which could be connected with its phase composition, higher surface area, stronger light harvesting and 1D rodlike morphology with short L/D ratio which may increase the separation efficiency of photogenerated electrons and holes.